Short-term spheroid culture of primary colorectal cancer cells as an in vitro model for personalizing cancer medicine. - Maria Jeppesen; Grith Hagel; Anders Glenthoj; Ben Vainer; Per Ibsen; Henrik Harling; Ole Thastrup; Lars N Jørgensen; Jacob Thastrup (PLoS ONE)
Chemotherapy treatment of cancer remains a challenge due to the molecular and functional heterogeneity displayed by tumours originating from the same cell type. The pronounced heterogeneity makes it difficult for oncologists to devise an effective therapeutic strategy for the patient. One approach for increasing treatment efficacy is to test the chemosensitivity of cancer cells obtained from the patient's tumour. 3D culture represents a promising method for modelling patient tumours in vitro. The aim of this study was therefore to evaluate how closely short-term spheroid cultures of primary colorectal cancer cells resemble the original tumour. Colorectal cancer cells were isolated from human tumour tissue and cultured as spheroids. Spheroid cultures were established with a high success rate and remained viable for at least 10 days. The spheroids exhibited significant growth over a period of 7 days and no difference in growth rate was observed for spheroids of different sizes. Comparison of spheroids with the original tumour revealed that spheroid culture generally preserved adenocarcinoma histology and expression patterns of cytokeratin 20 and carcinoembryonic antigen. Interestingly, spheroids had a tendency to resemble tumour protein expression more closely after 10 days of culture compared to 3 days. Chemosensitivity screening using spheroids from five patients demonstrated individual response profiles. This indicates that the spheroids maintained patient-to-patient differences in sensitivity towards the drugs and combinations most commonly used for treatment of colorectal cancer. In summary, short-term spheroid culture of primary colorectal adenocarcinoma cells represents a promising in vitro model for use in personalized medicine.